An Analysis of the Recommendations of the "Superstar" Money Managers at Barron's Annual Roundtable - Desai, Hemang; Jain, Prem C. (Journal of Finance, 1995)
We examine the performance of common stock recommendations made by prominent money managers at Barron's Annual Roundtable from 1968 to 1991. To avoid survivorship bias, we examine the performance of recommendations by all the participants. The buy recommendations earn significant abnormal returns of 1.91% from the recommendation day to the publication day, a period of about 14 days. However, the abnormal returns are essentially zero for one to three year post-publication day holding periods. Thus, an individual investing according to the Roundtable recommendations published in Barron's would not benefit from the advice.